Penerapan Metode Certainty Factor Dalam Mendiagnosa Dini Penyakit Telinga Hidung Dan Tenggorokan - Nurul Khasanah, Yustina Retno Wahyu Utami, Didik Nugroho (STMIK Sinar Nusantara, 2012)
This study aims to diagnose ENT (Ear Nose Throat) disease through a computer-based system. Often people do not understand about the disease, and doctors are limited in serving the community. For the expert, the expert system can be used as an inexperienced assistant. Also for substituting human knowledge in the form of the system, so it can be used by many people. This application will assist in finding a conclusion illness with appropriate prevention. The application system is analyzed data ENT diseases and symptoms of the ENT disease. The method used is the Certainty Factor. Application development using PHP and MySQL for the database. The results showed that the system is built to provide information to visitors about the type of disease and its definition, diagnose symptoms experienced visitors, danmemberikan initial solution treatment.Keyword: certainty factor, expert system, ENT disease